HUBUNGAN ANTARA KEMAMPUAN PENDENGARAN DAN RADIUS RUMAH PADA WARGA MASYARAKAT DI SEKITAR PLTD SIANTAN HILIR - ., Rendika Banitriono (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Electric power is the most fundamental need in supports peoplelife. The impact which emerge in the proccess of operati ng electric generatorwith diesel power (PLTD) is the noise which came from the diesel machi ne.Objective: This research was aimed to know the correlation between theability to hear and the distance of people houses around PLTD indownstrream Siantan.Methodes: This research was an analytic study with cross-sectional approach.92 subjects were chosen as sample by using cluster random sampling technique. Subjects were examined by usi ng tuning fork examination (ri nne,weber, and schwabach test) and were categori zed into normal group and hindrance group. According to the distance of people houses from PLTD indownstream Siantan, subjects were categorized into <100 meters and?100 meters. The data were analyzed by using Statistical Product and ServiceSolution 17.00 programme.Results: There was correlation that statistically significant between the abilityto hear and the distance of people houses around PLTD in downstream Siantan (P<0,027). The relati ve risk (prevalens ratio [RP] and the reliableinterval 95% [IK]) of hearing impairments on respondents who are at a radius of less than 100 meters was (RP 1,86; IK 1,072,37).Conclusion: There was corelation that statistically significant between the ability to hear and the distance of people houses around PLTD (electricgenerator with diesel power) in downstream Siantan. The house distance is the risk factor of hi ndrancing the ability to hear. In this case, subjects whosestated less than 100 meters from the PLTD have 1,9 times higher risk thansubjects whose stated more than equal to 100 meters from PLTD (electric generator with diesel power) in downstream Siantan.Keywords: the ability to hear, the house distance, noise induced hearing loss